1967
DOI: 10.1001/archneur.1967.00470240033003
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Patients With Petit Mal

Abstract: T HE PRESENT paper is based on a longterm study of 275 patients with petit mal. In this study an attempt was made to assess the incidence and character of other forms of epilepsy as they occur in patients with petit mal, to report the results of psychometric testing, and to obtain a critical insight into the problems of drug therapy and social prognosis for these patients. In addition, the genetic and other etiologic implications of the material will be discussed. Previous authors have covered some of these qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

1969
1969
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 8 publications
1
13
1
1
Order By: Relevance
“…Juvenile absence epilepsy (JAE)2 2429 was the likely diagnosis in four patients (cases [11][12][13][14]. Two patients (cases 11 and 12) had typical absences with onset at puberty.…”
Section: Generalised Tonic-clonic Seizuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Juvenile absence epilepsy (JAE)2 2429 was the likely diagnosis in four patients (cases [11][12][13][14]. Two patients (cases 11 and 12) had typical absences with onset at puberty.…”
Section: Generalised Tonic-clonic Seizuresmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Loss or severe impairment of consciousness is considered to be the clinical hallmark of absences.2021 EEG manifestations of typical absences, however, are frequently associated with mild, inconspicuous cognitive impairment. 22.24 Furthermore, typical absences have been studied in a uniform fashion' 19 25 26 despite existing evidence that their clinical and EEG features are syndrome-related.…”
mentioning
confidence: 99%
“…This is in contrast to previous studies that reported an evolution of generalized tonic-clonic seizures between 32% and 49%. 26,3234 This discrepancy might be due to our relatively short average follow-up period of 5.4 years, because there is a second manifestation peak of generalized tonic-clonic seizures usually 5 to 10 years after onset. 33 In addition, our strict adherence to the criteria of the International League against Epilepsy and the exclusion of children with atypical absences might have further reduced the number of generalized tonic-clonic seizures in our sample.…”
Section: Discussionmentioning
confidence: 90%
“…Embora apareçam em idades superiores à da instalação da síndrome, tais estados são mais precoces que os observados na epilepsia generalizada primária 4 . 5 . Outra diferença foi a falta de automatismos elaborados e a elevada incidência de hipotonia.…”
Section: Estados De Mal Epiléptico Não Convulsivos -Os Estados De Ausunclassified